Hydroxychloroquine Metabolites – An Exploratory Computational Study - Islam, Mohammed Monirul; Singh, Purna Sivarama; Rushd, Sayeed (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: HCQ has been found to provide the immunomodulation that helps to abate the possible cytokine storm response caused by the SARS COVID-19 virus and subsequent failures of major organs. It is also being used historically in treating Malaria and Rheumatoid arthritis and is known to be useful in cancer treatment. However, it shows a half-life of up to 70 days and has severe adverse effects including gastric disorders and retinopathy. Hypothesis: Therefore, we propose to explore some of its metabolites/ intermediates namely Desethyl hydroxychloroquine (DHCQ), Desethyl chloroquine (DCQ), and Bis-desethyl chloroquine (BDCQ) as alternate drug systems with minimized toxicity. Results and Discussion: The structural and spectral studies of these lead compounds to be unraveled using computational modeling and the evaluation of ADME parameters such as absorption, distribution, metabolism, and excretion would be performed using the SwissADME tool to assess the drug-likeness and medicinal chemistry friendliness. The future scope of the work involves the docking studies of these compounds to assess the therapeutic compliance for the treatment of viral infections and rheumatoid arthritis.
Keywords: Hydroxychloroquine metabolites; COVID-19 drugs; Computational; ADME; studies; Rheumatoid arthritis; Immunomodulation